The Interplay between Fractional Calculus and Complex Analysis - Bouzouina, Chaima (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
The usual definitions of fractional derivatives and integrals are very well-suited for a fractional generalisation of real analysis. But the basic building blocks of complex analysis are different: although fractional derivatives of complex-valued functions and to complex orders are well known, concepts such as the Cauchy–Riemann equations and d-bar derivatives have no analogues in the standard fractional calculus. In the current work, we propose a formulation of fractional calculus which is better suited to complex analysis and to all the tools and methods associated with this field. We consider some concrete examples and various fundamental properties of this fractional version of complex analysis. Keywords: fractional derivatives, complex analysis, d-bar derivatives, Leibniz rule

ÖZ: Kesirli türevlerin ve integrallerin olagan tanımları, gerçek analizin kesirli bir ˘ genelle¸stirilmesi için çok uygundur. Ancak kompleks analizin temel yapı ta¸sları farklıdır: kompleks degerli fonksiyonların kesirli türevleri ve kompleks emirler iyi ˘ bilinmesine ragmen, Cauchy-Riemann denklemleri ve d-bar türevleri gibi kavramların ˘ standart fraksiyonel kalkülüste analogları yoktur. Mevcut çalı¸smada, kompleks analize ve bu alanla ili¸skili tüm araç ve yöntemlere daha uygun kesirli kalkülüsün formülasyonunu öneriyoruz. kompleks analizin bu kesirli versiyonunun bazı somut örneklerini ve çe¸sitli temel özelliklerini göz önünde bulunduruyoruz. Anahtar Kelimeler: kesirli türevlerin, kompleks analiz, d-bar türevleri, Leibniz kuralı.
Doctor of Philosophy in Mathematics. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2021. Supervisor: Asst. Prof. Dr. Arran Fernandez.
Keywords: Mathematics; Applied Mathematics and Computer Science; Fractional Calculus; Fractional derivatives; complex analysis; d-bar derivatives; Leibniz rule